MENINGKATKAN KEMAMPUAN LOGIKA MATEMATIKA ANAK MELALUI PEMBELAJARAN TERPADU DI TAMAN KANAK-KANAK - Neni Neni; Ema Aprianti (IKIP Siliwangi, 2020)
Integrated learning provides meaningful learning concepts that are learned by children. This is seen from its development so that children learn easily and meaningfully. The purpose of the research is to improve mathematics learning, the benefits, the influence on children's lives, the development of thinking power through mathematics. Integrated Learning For Kindergarten Children, consisting of integrated learning for kindergarten children, integrated learning principles, and the characteristics and benefits of integrated learning. The role of the teacher is so helpful in achieving learning that is set or in accordance with expectations, mathematical concepts that can be learned through playing while learning. This type of research is a qualitative study using data collection techniques as follows: observation, interviews, documentation and literature studies. The data collected from this study is that the process of improving mathematical abilities in kindergarten children through improved integrated learning abilities can help children's cognitive development well. The results showed the application of integrated learning for mathematics learning can improve mathematical logic abilities.Pembelajaran terpadu memberikan konsep belajar yang bermakna yang dipelajari oleh anak. Hal ini dilihat dari perkembangannya supaya anak belajar dengan mudah dan bermakna. Tujuan penelitian adalah untuk meningkatkan pembelajaran matematika, manfaat, pengaruh Terhadap Kehidupan Anak, Pengembangan Daya Pikir Melalui Matematika. Pembelajaran Terpadu Untuk Anak Taman Kanak-Kanak, terdiri dari Pembelajaran terpadu untuk Anak Taman Kanak-Kanak, Prinsip-prinsip pembelajaran terpadu, serta ciri-ciri dan manfaat pembelajaran terpadu. Peranan pengajar begitu membantu dalam ketercapaian pembelajaran yang ditetapkan atau sesuai dengan harapan, konsep matematika yang dapat dipelajari melalui bermain sambil belajar. Jenis penelitian ini adalah penelitian kualitatif yang menggunakan tehnik pengumpulan data sebagai berikut: observasi, wawancara, dokumentasi dan studi literatur. Data terkumpul dari penelitian ini adalah bahwa proses meningkatkan kemampuan matematika pada anak TK melalui peningkatan kemampuan pembelajaran terpadu dapat membantu perkembangan kognitif anak dengan baik. Hasil penelitian menunjukan penerapan pembelajaran terpadu untuk pembelajaran matematika dapat meningkatkan kemampuan logika matematika.